Pengaruh Literasi Keuangan dan Persepsi Risiko terhadap Kesadaran Pajak melalui Penggunaan E-wallet - Winan Kristin Tambunan; Serly Veronica; Winestia Winestia; Candyce Candyce; Yohana Yemima Sihotang; Dona Angelina Lawrence (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The rapid advancement of digital financial technology has increased the adoption of e-wallets among university students and may influence tax awareness through greater transparency in digital transactions. This study examines the effects of financial literacy and risk perception on tax awareness through e-wallet usage among higher education students in Batam City, with culture included as a control variable. A quantitative survey was conducted involving 247 students who regularly use e-wallet services. Data were analyzed using multiple linear regression with robust standard error estimation in Google Colaboratory. The results indicate that financial literacy has a positive but insignificant effect on e-wallet usage (β = 0.0411, p > 0.05), whereas risk perception has a positive and significant effect (β = 0.5572, p < 0.01). E-wallet usage also positively and significantly affects tax awareness (β = 0.4613, p < 0.01). Furthermore, e-wallet usage significantly mediates the relationship between risk perception and tax awareness but does not mediate the relationship between financial literacy and tax awareness. These findings suggest that e-wallet adoption is driven more by digital lifestyle demands than financial literacy and that improving digital risk literacy may help strengthen students’ tax awareness and responsible use of financial technology.